A Review on Zingiber capitatum Roxb. - Ms. Pallavi Maruti Patil; Dr. Vanita G. Kanase (International Journal of Pharma and Bio Sciences, 2021)
Zingiber capitatum Roxb is found in numerous places of India and their therapeutic capacity have been extensively examined and acknowledged in numerous conventional system. Various literature has conducted the pharmacological activity in- vitro and in–vivo which proven to have antioxidant and antimicrobial from extracts of rhizomes. Ginger is a vigorous anti-oxidant substance and may either alleviate or prevent generation of free radicals. It is considered a secure herbal medicine with minimum side effects. The medicinal properties of this plant are mainly due to the presence of gingerol, shogaols, paradol, etc which represent it as a beneficial source of medicinal compound. Preliminary phytochemical analysis depict the presence of phytoconstituents introduced in the literature such as alkaloid, cardiac glycoside, carbohydrates, tannin, saponin, ascorbic acid, phenols and flavonoids. Currently, there’s an interest in ginger and a lots clinical experiments are accomplished extensively for the isolation, identification of active constituents and scientific verification of its pharmacological for the treatment of several disease and conditions. This article aims at reviewing the most salient recent reports on these investigations that deals with botanical and ayurvedic classifications, different pharmacological activity, cultivation, medicinal uses and chemical composition of essential oils from rhizomes of Zingiber capitatum as indicated by ayurveda and modern science. The study elaborates; ginger is effective in contagion diseases and revitalizing the body at disease conditions according to both of Ayurveda and modern concepts through increasing appetite, immunity and re-boosting weakened physiological functions of the human body. We hope that this updated review can appeal a more awareness to Zingiber capitatum Roxb and its further applications, together with its potential to be developed into functional foods or nutraceuticals for the precautionary and control of chronic diseases.